Association between keratin 8 expression and immune-related pneumonitis: a case-control study in lung adenocarcinoma patients - Wang, Xuena; Yang, Yang; Guo, Hongxia; Li, Xu; Sun, Yue; Mei, Qi; Ma, Yuhui (Frontiers in Immunology, 2025)
BackgroundImmune-related pneumonitis (IRP) is a serious adverse event observed in lung adenocarcinoma patients undergoing immunotherapy. Previous studies have revealed that high Keratin 8 (KRT8) expression is associated with poor prognosis in these patients. However, the potential link between KRT8 expression levels and the risk of developing IRP remains unclear. This study aims to explore the correlation between KRT8 expression and IRP risk in lung adenocarcinoma patients receiving immunotherapy.MethodsA case-control study was conducted involving 36 lung adenocarcinoma patients (12 IRP cases and 24 age- and sex-matched controls without IRP) receiving immunotherapy. Tumor tissue samples were analyzed for KRT8 expression using immunohistochemistry. A multivariate logistic regression analysis was performed to evaluate the relationship between KRT8 expression and IRP risk.ResultsKRT8 expression was significantly higher in the IRP group compared to controls (12.9 ± 8.2% vs 5.6 ± 5.2%, adjusted P = 0.03). Multivariate analysis revealed that each percentage increase in KRT8 expression was associated with a 32% increased risk of developing IRP (OR = 1.32, 95% CI: 1.09-1.61, P = 0.005). Compared to the lowest tertile, the moderate KRT8 expression tertile showed no significant association with IRP risk, while the highest tertile demonstrated a significant 14-fold increased risk of developing IRP.ConclusionElevated KRT8 expression in tumor tissues is significantly associated with increased IRP risk in lung adenocarcinoma patients receiving immunotherapy. These exploratory, hypothesis-generating findings suggest that KRT8 expression may serve as a potential biomarker for predicting IRP development, though validation in larger cohorts is needed.